Manusia di Era Kebudayaan Digital: Interpretasi Ontologis Martin Heidegger - Oktarizal Drianus (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
The aims of paper is digging beneath the ontological relations between human and technology. It is handled by drawing a inspiration from Martin Heidegger's thought, specifically the period of Heidegger II. This library research discusses two key of Heidegger’s texts against technology, namely: “Questions concerning Technology” and “Discourse about Thinking”. The paper provides some findings: 1) The Dasein reconstruction transforms toward Digi-sein as the only and one Questioner of Being that exist within a heart of digital culture; 2) Heideggerian destruction of gestell as a framed way of thinking that makes humans and technology relations become non-free relations. Heidegger calls calculative thinking as actually